Implementation of teledentistry during the COVID-19 pandemic at Bandung community health centers - Assagaff, Syarifa Salsabila; Suryanti, Netty; Setiawan, Asty Samiaty (Faculty of Dentistry, Universitas Gadjah Mada, 2022)
Teledentistry has gained an increasing popularity among dentists as an alternative innovative solution to minimize the risk of the transmission of COVID-19 and other infections. Dentists at the Bandung community health center have started implementing teledentistry since the government issued a reference for dental and oral health services during the pandemic. The purpose of this study was to analyze the implementation of teledentistry in community health centers based on the references issued by the government. The population consisted of dentists who implemented teledentistry during the COVID-19 pandemic at the Bandung community health centers. There were 26 respondents as the research samples who were selected using a non-probability sampling technique. This was cross-sectional descriptive research which used an online questionnaire regarding the implementation of teledentistry based on the Technical Guidelines for Dental and Oral Health Services from the Ministry of Health of the Republic of Indonesia. The implementation of teledentistry includes teleconsultation, telediagnosis, teletriage, telemonitoring, teleeducation, communication tools, provision of prescriptions and referrals, service fees, and medical records. The data analysis was carried out by presenting the results of the teledentistry implementation, namely the types of teledentistry implemented by the dentists were teleconsultation 100%, telediagnosis 92.3%, teletriage 76.9%, telemonitoring 7.7%, teleeducation 92.3%; 100% carried out teledentistry via short messages, 76.9% had given prescriptions, and 80.7% had given referrals, 84.6% did not charge any service fee, and only 57.6% recorded medical records. The implementation of the teledentistry services during the COVID-19 pandemic at the Bandung Community Health Centers has not been optimal because the regulation has not been well socialized. In addition, there has been no legal certainty and laws governing teledentistry in Indonesia.